Cyber Security Politics 2022
DOI: 10.4324/9781003110224-1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: In the past decade, cyber security has consolidated its position as one of the top national security issues of the 21st century: The dynamic interaction between technological vulnerabilities and the possibilities of their political misuse creates a problem space with little stability. Due to enduring uncertainties about the scope and tempo of ongoing socio-technological transformations, an increasing willingness to use disruptive cyber tools in the context of great power rivalry, and significant fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…One of the main problems in cybersecurity, meaning in terms of digitalisation, is the low stability. 57 Contemporary politics is therefore forced to address the issues and challenges for the purpose of managing cybersecurity. Due to the function of cyber security, its complexity and challenges are transboundary.…”
Section: Insights Into Cybersecurity In Terms Of Digitalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main problems in cybersecurity, meaning in terms of digitalisation, is the low stability. 57 Contemporary politics is therefore forced to address the issues and challenges for the purpose of managing cybersecurity. Due to the function of cyber security, its complexity and challenges are transboundary.…”
Section: Insights Into Cybersecurity In Terms Of Digitalisationmentioning
confidence: 99%
“…79 The literature showed that a relevant and effective policy setting in terms of cyber security leads to a more fluid sovereignty when the non-state actors, social groups, individuals, or state actors could affect the state stability or the overall stability of the government. 80 On the other side, the practice could be still challenging. Nowadays, the debate on cybersecurity and the cooperation among the states is more cardinal than before, especially with the raising trends of cyberspace militarisation and because of the evidence of cyber-attacks.…”
Section: Insights Into Cybersecurity In Terms Of Digitalisationmentioning
confidence: 99%